COVID-19 pandemic: A multidisciplinary perspective on the pathogenesis of a novel coronavirus from infection, immunity and pathological responses - Yi, Jia; Miao, Jiameng; Zuo, Qingwei; Owusu, Felix; Dong, Qiutong; Lin, Peizhe; Wang, Qilong; Gao, Rui; Kong, Xianbin; Yang, Long (Frontiers in Immunology, 2022)
Coronavirus disease 2019 (COVID-19), caused by severe acute respiratory syndrome coronavirus2 (SARS-CoV-2), has spread to more than 200 countries and regions, having a huge impact on human health, hygiene, and economic activities. The epidemiological and clinical phenotypes of COVID-19 have increased since the onset of the epidemic era, and studies into its pathogenic mechanisms has played an important role in clinical treatment, drug development, and prognosis prevention. In this paper, we review the research progress on the pathogenesis of the novel coronavirus (SARS-CoV-2), focusing on the pathogenic characteristics, loci of action, and patho-genic mechanisms leading to immune response malfunction of SARS-CoV-2, as well as summa-rizing the pathological damage and pathological manifestations it causes. This will update researchers on the latest SARS-CoV-2 research and provide directions for future therapeutic drug development.